Evaluasi User Interface (UI) Dan User Experience (UX) Sistem Informasi Gudang Obat Rumah Sakit Siti Khodijah Menggunakan Lean UX - AlFatich, Achmad Bayu AlBait; Sodik, Anwar (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
The digital era, which has rapid-advancing technology, requires adjustments to existing systems. These adjustments also occur at Siti Khodijah Hospital, specifically in the drug warehouse information system. This research evaluates the hospital's drug warehouse system using the Lean UX method to enhance user comfort in the system. Lean UX is an iterative method consisting of four stages: declaring assumptions, creating an MVP (minimum viable product), running experiments, and receiving feedback and research. During the stage of running an experiment, the author employed the SUS (System Usability Scale) method. SUS includes 10 questions related to user comfort, administered to 15 system users. This study resulted in three iterations of design recommendations, each yielding different testing scores. The first iteration scored 67.5 and the second iteration scored 73.8, both categorized as good. Meanwhile, the third iteration scored 80.3, categorized as excellent. The third iteration became the last one in the Lean UX method stage since the testing score met the research target value.